(untitled) (Journal of Mathematics Mechanics and Computer Science, 2011)
By analyzing boundary conditions of two types from number of multidimensional problems for parabolic by Petrovskii systems illposed ones are selected. Then these problems are reduced to the conditionally well-posed ones.